IMPLEMENTASI BOOSTER 4G LONG TERM EVOLUTION (LTE) PADA PROVIDER TRI DI GEDUNG F POLITEKNIK NEGERI PADANG - Widiansyah, Iqwan; Aulia, Siska; Yustini, Yustini (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
This study examines the quality of 4G LTE that operates indoors, namely at Gedung F Politeknik Negeri Padang, where initial testing reveals extremely low Reference Signal Received Power (RSRP) of about 36.86% due to physical stress. The primary goal of this study is to analyze 4G LTE quality based on RSRP, RSRQ, and SINR parameters before and after booster implementation, as well as to identify technical and environmental factors that affect kinerjanya. The technique used involves using a 4G LTE booster from Tri with an omnidirectional antenna, a log-periodic antenna, and a pengulang amplifier. Data is collected using the walk test method using the TEMS Pocket lunak perangkat, and it is analyzed using TEMS Discovery. The study's findings indicate a significant increase, with the rata-rata RSRP rising from 34.86% before to pemasangan to 97.83% in F304, 47.40% in F305, and 65.95% in koridor. RSRQ also shows improvement, with 91.44% becoming 100% in F304 and koridor and 99.74% in F305, while SINR remains stable at 100% in all locations. In summary, 4G LTE boosters are effective in improving signal quality, especially in the RSRP parameter, therefore they can improve data service availability in areas with worse signal quality.